NATIONALISM IN VIETNAM AND KOREAN LITERATURE IN THE LATE 19TH AND EARLY 20TH CENTURIES: CASES OF PHAN BOI CHAU AND SHIN CHAE-HO - Ngoc, Tran Tung; Thu, Nguyen Le (VNU Journal of Foreign Studies; Vol 37 No 2DO - 10.25073/2525-2445/vnufs.4701, 2021)
East Asian literature in the early twentieth century witnessed the emergence of many great authors who gathered all personality of a patriot - writer - historian - revolutionary activist. They emphasized literature does not serve artistic purposes, but social purposes, which touch the heart. Literature at this time conveyed the stream of national consciousness, nationalism, independence and freedom to all of the people and promoted their patriotism and the spirit of fighting for the nation and the people. This paper focuses on analyzing the nationalist ideology in the works of Phan Boi Chau and Shin Chae-ho in the history of literature of Vietnam and Korea in the early twentieth century. Thereby, the research provides an overview of the common characteristics of the nationalist literature in East Asia. In the research content, this paper recognizes the nationalist ideology of Korean and Vietnamese intellectuals in the transformation of the historical, political and social situation in the early twentieth century. On that basis, this paper identifies the characteristics of nationalism in Shin Chae-ho’s and Phan Boi Chau's works.